Eliminasi Waste Pada Proses Produksi Malt Powder Dengan Metode VSM dan VALSAT (Studi Kasus PT. XYZ) - Desy Rosarina; Sri Lestari; Johan Candra Dinata (Universitas Muhammadiyah Tangerang, 2022)
The background of this research is that there is still waste in the malt powder production process, as evidenced by the results of the questionnaire which show 17% waste defect, 16% inventory and 15% waiting. This study aims to identify waste in the malt powder production process using a lean manufacturing approach and the tools used in this study are value stream mapping (VSM) and value stream analysis tools (VALSAT). The initial stage is to create a value stream mapping curent state, then analysis using process activity mapping (PAM) to identify types of activities such as value added (VA), non value added (NVA) and necesary non value added. From the analysis, the value added ratio is 55.44%. Then perform waste analysis with supply chain response matrix (SCRM) and then analyze waste with quality filter mapping (QFM) for defect types of waste. The percentage of delay activity was 7.09%, where this activity was included in non-added value (NVA) activities and the results of the SCRM analysis of the raw material storage area were 1, 03, the production process area was 0.13 and the finished goods storage area was 0.96. Then the time to fulfill the order fulfillment of malt powder is 47 days with the cumulative physical stock days of 2.1 days. Keywords: Lean Manufacture, Value Stream Mapping, Value Stream Analys Tools, Process Activity Mapping, Lean Production